Excavating the Modern Self: Haggard’s Egyptological Romances - Nolwenn CORRIOU (E-REA, 2020)
Henry Rider Haggard’s Egyptomania took many shapes, from regular journeys to Egypt to extensive collections of ancient Egyptian artefacts. This article looks more particularly at Haggard’s representation of ancient Egypt in his literary works and at the implications of his narrative choices in the scientific and imperial context in which he wrote his Egyptological romances. By establishing genealogical links between ancient Egypt and modern Britain through the literary form of archaeological fiction, Haggard constructs a palimpsestic vision of individual and collective history that can be read both in psychoanalytical and in imperial terms. This paper examines the place Egypt occupies in Haggard’s imagination by considering some of the narrative and narratological elements shared by his Egyptological romances, with a particular focus on The Ancient Allan and “Smith and the Pharaohs”. The depiction of Egypt as an oneiric place located within the Victorian mind and as the origin of a layered modern identity suggests an ambivalent interpretation of Haggard’s imperialist stance at the turn of the twentieth century.